Susceptibility of Echinochloa crus-galli Biotypes from Rice Crop to Profoxydim and Impact of the Weed Growth Stage - Panagiotis Kanatas (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Barnyardgrass (Echinochloa crus-galli) is one of the most problematic weeds on rice crop. The research was to evaluate the response of several barnyardgrass biotypes from Greece to profoxydim and evaluate the role of different rates and growth stages on the overall effectiveness. Three experiments were conducted in 2018. The response of the several biotypes had high variability (20-100%), with the most susceptible biotypes originating from regions in which crop rotation is a common practice (Fthiotida). Moreover, dose-response experiments showed that the rate of profoxydim required to adequately control the resistant population G17 was 4-times higher than the maximum recommended dose. Concerning the phenology effect on profoxydim effectiveness, This study revealed a higher efficacy at the earlier growth stage BBCH 13 (15-50% higher than growth stages BBCH 22 and 30), probably it was due to the smaller size and the higher growth rate of the younger plants. Consequently, the significant effect of weed growth stage on the effectiveness of profoxydim implies that application of the herbicide at earlier growth stages could optimize herbicide use and result in a better control with the condition of avoidance crop injuries.